Industry 5.0: Spectrum or Entity? - Gupta , Sanjiv (Gyan Management Journal, 2023)
The fast pace of innovation in technology is shrinking the world.  The digital technology of Industry 4.0 has reduced the role of human  beings and boosted automation. The world is on the threshold of using  technology of industry 5.0 commercially with the advantage of human  interaction from the technology of Industry 4.0. This research paper  analyses the current state of industry 4.0 and future implications of  industry 5.0 in the dynamic business environment. One emerging  theme is Human- Robot coworking. There is an emphasis on  sustainable and resilient production systems. The main aim of the  researcher is to determine whether industry 5.0 is truly human centric  and also to look at the changes the first and third world countries are  likely to face during the implementation of industry 5.0. with the aim  of achieving sustainable processes.
Keywords: Industry 4.0; Industry 5.0; Human– Robot collaboration; Cyber–physical systems